Quantifying the partial and general equilibrium effects of sanctions on Russia - Lisandra Flach; Inga Heiland; Mario Larch; Marina Steininger; Feodora A. Teti (Review of International Economics, 2023)
This paper evaluates the effects of sanctions on Russia between 2014 and 2019 and the resulting countersanctions. We estimate their impact on trade in a gravity framework, allowing for treatment heterogeneity among pairs and sectors, and use the estimated elasticities in a general equilibrium analysis. We find that the sanctions decreased trade with Russia in key sectors, translating to a loss in real income in Russia by 0.3%. Full decoupling of the EU and its allies from Russia would increase this effect to over 4%. Our results emphasize the role of deep sanctions as a foreign policy instrument and international cooperation.
Keywords: F1; F13; F14; F5; F51; H5; N4; 330; general equilibrium; sanctions; structural gravity; treatment heterogeneity